FINANCIAL INCENTIVE GAIN E-COMMERCE’S COSTUMER – A STUDY FOR SEREY TO ENTER INDONESIAN MARKET - Muhammad Ali Ridlo Nova Putra; Chhay Lin Lim; Surya Raharja (Diponegoro Journal of Accounting, 2022)
E-commerce is one of the platforms that is being intensively in Indonesia. Offering many promotions is one way to attract the attention of its customers and can increase the users of the platform. The most popular method in using incentive is providing free shipping unto giving cashback to customers. This research studies how the revenue design is formed from providing financial incentives from E-commerce to its customers. This research also provides information, opportunities, and challenges to other platforms by providing financial incentives by analyzing scientific journals and articles and give questioner to Indonesian customer who ever use Indonesian marketplace in this case Tokopedia. After doing this research, and it can be seen what the revenue design looks like, it can be applied to other platforms by providing incentives that will increase the number of e-commerce custom.